A Novel Virtual Nasal Polyp Removal System Based on Computed Simulation - Silva Freitas, Marcelo de Castro; Oliveira Sousa, Fábio; Guimarães Batista, Josias; Ripardo de Alexandria, Auzuir; Cavalcanti Neto, Edson; Silveira Cavalcante, Tarique; Timbó Gondim, Victor José; Correia Nogueira, Ingrid; Sales, Emanuela; Azevedo, Glauco; Carvalho Reis, Marcello; Costa Albuquerque, Victor Hugo (Journal of Mechatronics Engineering, 2024)
This paper proposes a simulation platform to train and study the specific nasal polyp removal procedure using a human anatomy atlas in the three-dimensional (3D) model, the Unity3D real-time development platform, this paper also compares articles in the field of simulation applied to medical studies. The standard procedure to remove paranasal polyps is Functional Endoscopic Surgery of the paranasal sinuses. A rigid optical fiber that guides the removal of polyps through instruments to restore adequate sinus drainage. Currently, many simulators are designed to simulate the performance of medical procedures such as these. The main purpopse is to provide a new solution for training, planning and testing Medical procedures. Using the aforementioned platform, we built a polyp model using the virtual physics system called Metaball, together with Atlas3d we explored the anatomy of the six paranasal organs and we simulate their removal. The simulator applies the concepts of gamification, using the mouse and keyboard control system with a graphical interface for changing tools and timer. The tools were developed to simulate cutting and suction, functions common during the actual procedure. After field testing using the TAM and SUS, we obtained a satisfactory result of 80%, grade B. Finally, the results obtained through the techniques performed, presenting the functionality and usability of the software, and also a comparison of the systems developed in this study with the current works that follow the same theme. This preliminary study demonstrates the potential that culminated in the creation of an environment for the removal of paranasal polyps, partially validated by teachers and students, who had active and constant participation throughout the process, whether in the development of tools, of clinical cases, or in the training carried out.